Letter from S.S. Dilman to James Curtis Booth, August 26, 1854 - Dilman, S. S. (1854)
S. S. Dilman inquires about becoming a student of James Curtis Booth (1810-1888).
Keywords: Booth, James Curtis, 1810-1888; Chemistry teachers